1999
DOI: 10.1046/j.1440-1584.1999.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes in an Aboriginal Community: A Comparison With the Surrounding Rural Area

Abstract: Antenatal, intranatal and postnatal features of all Aboriginal women who lived at Cherbourg Aboriginal Community and delivered during 1990, 1991 and 1992 were compared with all non-Aboriginal women in the same rural area who delivered at Kingaroy Base Hospital during 1991. Almost all the Aboriginal women also delivered at Kingaroy. The data for 146 Aboriginal and 139 non-Aboriginal women were taken from the hospital records. The Aboriginal women were generally younger at delivery (Aboriginal 35% younger than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…This finding is somewhat consistent with several studies that found high rates of sexually transmitted infections (STIs) among Indigenous women of reproductive age living in rural communities 37,38 and pregnant Indigenous women living in urban areas. 39 Early diagnosis and treatment of syphilis has been shown to be associated with similar risk of stillbirth as the general uninfected population.…”
Section: Perinatal Infectionsupporting
confidence: 92%
“…This finding is somewhat consistent with several studies that found high rates of sexually transmitted infections (STIs) among Indigenous women of reproductive age living in rural communities 37,38 and pregnant Indigenous women living in urban areas. 39 Early diagnosis and treatment of syphilis has been shown to be associated with similar risk of stillbirth as the general uninfected population.…”
Section: Perinatal Infectionsupporting
confidence: 92%
“…The survey did not attempt to capture clinical data, nor did it measure a number of lifestyle factors known to contribute to poor perinatal health outcomes in Indigenous populations. These data are available elsewhere [79-81] and were not the focus of this study. Rather, the focus of this study was to investigate how maternity care was evaluated by Aboriginal and/or Torres Strait Islander women to inform improvements in service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by several studies that 86 found high rates of sexually transmitted infections (STIs) among Indigenous women of reproductive age living in rural communities [217,218] and pregnant Indigenous women living in urban areas [219]. Similarly, a population based study in Western Australia found infection to be an important cause of death for Indigenous infants [220].…”
Section: Perinatal Infectionmentioning
confidence: 74%
“…217 The aetiology of stillbirth is varied, however, placental dysfunction has been suggested an important pathway [326] in the development of pre-eclampsia/eclampsia, fetal growth restriction and placental abruption [252]. Further research into the aetiology of placental dysfunction resulting in fetal death at later gestational ages could be useful in addressing the large proportion of term stillbirths with unknown cause of death.…”
Section: Term Antepartum Stillbirth Risk Predictionmentioning
confidence: 99%